Being Skeptical? Exploring Far-Right Climate-Change Communication in Germany. Issue 5 (4th July 2018) - Forchtner, Bernhard; Kroneder, Andreas; Wetzel, David
ABSTRACT: This article explores climate-change communication by the German far right – spanning a continuum which ranges from anti-liberal democracy radical-right populists, to the extreme right and to anti-democratic neo-Nazis – and asks: how do these actors articulate the phenomenon of climate change? In responding to this question, we conduct a discourse network analysis which identifies relations between actors, objects, phenomena, and processes, and points out differences/similarities across a continuum of exemplary far-right sources. The investigated actors put forward a rather skeptical climate change narrative, even though differences exist as the significance attached to the Volk and its sovereignty, rooted in far-right ideology, sometimes overrides, and sometimes is in harmony with, their ideological-driven affinity with nature protection. We thus contribute to the growing body of knowledge on climate-change communication and, more specifically, on the link between ideology and climate-change skepticism.